Sociodemographic and Etiological Factors in Men with Sexual Failure in Wedding Night - Ahmed Al-Jiboori, Saadoun D. (Zanco Journal of Medical Sciences (ZJMS), 2009)
Background and objective: Honeymoon sexual dysfunctions mean the inability of men to do first sexual intercourse with their virgin wives. Immediate causes include performance anxiety or fear of failure, lack of adequate stimulation, and relationship conflict. To study the sociodemographic and etiological factors concerning men sexual failure in wedding night. Methods: The study was undertaken between the period of December 2004 and December 2007 at Azadi general hospital, which included 60 male patients presented to the psychiatric out-patient clinic with the chief complaint of sexual failure in wedding night and in whom organic causes had been excluded. Results: The commonest age of patients were between 25-29 years (55%) , most of whom were educated below secondary school(57%), unskilled worker(58%) and from rural area (73%). 50% of them were presented more than one month. The commonest fear was fear of failure (67%) and the commonest sexual dysfunction was erectile failure (90%). 72% of patients contributed their problem to witchcraft, evil eye and jinn possession, while 7% of them contributed their problem to psychological causes. 22% of patients had previous history of consultation with non psychiatric physician for their problem, while 67%of them had previous history of contact with healers.73% of patients, their marriage were traditionally arranged and most of couples (75%) had rarely contact during engagement. 88% of patients had spent their wedding night at their primary family home,13% of them had foreplay before intercourse and only 3% had previous past sexual experience. Conclusion: Men sexual dysfunction caused by the interaction of multiple factors, mainly psychological, social, cultural and educational level.